Microbial Biomarkers Helpful in Early Detection of Cancer: Prognosis and Suitable Treatment - Khalid, Abdul Karim; Hafeez, Fahad; Qalandar, Shahbaz; Fatima, Hejab; Muhammad Saqib; Ali, Usman; Imran, Faria; Awais, Hafiz Muhammad; Muhammad Faizan; Hussain, Ahram (Indus Journal of Bioscience Research, 2024)
The significance of microbial biomarkers in cancer detection and prognosis garners heightened interest, with considerable implications for early diagnosis, tailored treatment, and enhanced patient outcomes. Microbial dysbiosis, especially within the gut microbiome, is associated with multiple cancers, including gastrointestinal, colorectal, and pancreatic malignancies. Notwithstanding the expanding corpus of research, the methods through which microbial biomarkers affect cancer development and treatment response remain inadequately comprehended, and their clinical use is currently being explored. This review consolidates information on microbial biomarkers in cancer, emphasizing their significance in early detection, prognosis, and therapy results. The review rigorously assesses studies investigating microbial fingerprints as prospective diagnostic instruments and scrutinizes the constraints of current research, encompassing challenges associated with repeatability, validity, and clinical integration. Recent research highlights key results about new microbial biomarkers that demonstrate potential for early detection and may impact patient prognosis and therapy efficacy. The review identifies critical gaps in the field, notably the necessity for standardized methodology, expanded clinical trials, and an enhanced mechanistic comprehension of microbiome-cancer interactions. The analysis ultimately proposes actionable recommendations for future research, emphasizing the integration of microbiome data with improved diagnostic tools and tailored therapy strategies. This review seeks to address existing research gaps to facilitate the creation of microbiome-based diagnostic systems that enhance traditional cancer screening and improve clinical outcomes.